2021
DOI: 10.1111/tbed.14049
|View full text |Cite
|
Sign up to set email alerts
|

Infection with Nannizziopsis guarroi and Ophidiomyces ophiodiicola in reptiles in Taiwan

Abstract: Fungal infection is an emerging threat to reptiles. The main pathogens are fungi of the genera Nannizziopsis, Paranannizziopsis and Ophidiomyces. The clinical symptoms range from mild skin lesions to the dissemination of internal organs and even death. Most of the reported cases are from Europe, North America and Australia. In this study, we report the Nannizziopsis guarroi infection in one captive inland bearded dragon (Pogona vitticeps), one captive green iguana (Iguana iguana) and Ophidiomyces ophiodiicola … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 28 publications
5
37
0
3
Order By: Relevance
“…Similar to previous studies that had examined only a small number of loci [26, 27], we identified three major clades among all 82 sampled Oo strains, but all strains originating from wild snakes in the USA belonged to a single clade (Clade II). Within this North American clade, we initially observed what appeared to be high genetic diversity as evidenced by the presence of many long phylogenetic branches (Fig.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Similar to previous studies that had examined only a small number of loci [26, 27], we identified three major clades among all 82 sampled Oo strains, but all strains originating from wild snakes in the USA belonged to a single clade (Clade II). Within this North American clade, we initially observed what appeared to be high genetic diversity as evidenced by the presence of many long phylogenetic branches (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…S1). This represented ~81-84% of the annotated protein coding genes for each strain, and the overall topology, which consisted of three, well-supported main clades, was consistent with previously published phylogenies for Oo [26,27]. One of these clades (Clade I) contained all four strains isolated from wild snakes in Europe; a second clade (Clade II) contained all 65 strains isolated from wild snakes in North America as well as 10 strains from captive snakes; and the third clade (Clade III) included three strains, all collected from snakes in captivity.…”
Section: Phylogenetic Analysissupporting
confidence: 88%
See 2 more Smart Citations
“…O. ophidiicola is a generalist fungus and is known to infect a wide range of snake species with different ecologies irrespective of taxonomy and habitat (33). First reported in the mid-2000s, but likely present as early as the 1940’s (3436), SFD has since been documented in more than 30 species of wild snakes in the United States and Europe (31) and instances of SFD have also been reported in Australia (37) and South East Asia (38, 39). Clinical signs of ophidiomycosis vary among individuals, from general signs such as lethargy, skin lesions, excessive shedding, to crusts, granulomas, corneal opacity, and ulcers on the head and body in more severe cases (29).…”
Section: Introductionmentioning
confidence: 99%